Cell-mediated immunity in weaned pigs - Blecha, Frank; Pollmann, D.S.; Nichols, David A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The stress of weaning lowers cellular immune reactivity in 2-, 3- and 4-week-old pigs. However, pigs weaned at 5 weeks of age do not exhibit altered cell-mediated immune reactivity. Those changes could alter disease susceptibility in young pigs.
Keywords: Swine; Cell-mediated immunity; Weaned pigs